Measuring Digital Literacy Among Micro and Small Enterprises (MSEs) in Indonesia: Case Study From Pontianak City - Arninda, Arninda; Darusman, Darusman; Supandih, Fathia Alya (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: The rapid changes in people’s consumption behavior resulting from technological and information advancements require business actors to have a high level of digital literacy to increase sales performance. Purpose: This study aims to measure the level of digital literacy among micro and small-scale businesses particularly in the vibrant region of Pontianak City. Design/Methodology/Approach: Primary data are taken from non-formal MSEs category of business as they make up the largest share of business ownership category in the region. This study employs descriptive qualitative research through grand mean methodology which is accurate to analyze the distinct characteristic across multiple groups of samples, as well as to facilitate interpretation of unchanging effects by controlling of inclusive variability. Conclusion: This study finds that the level of digital literacy among MSEs in Pontianak City is categorized into upper-middle group with average total score of 3.64 where micro-scale enterprises are found to have lower level of literacy as compared to small enterprises. It is also found that imbalance of digital literacy within variables used in this study. Internet searching variable (X1) and hypertextual navigation (X2) and knowledge assembly (X4) variable are found to be in the category of upper-middle group, while content evaluation variable (X3) is found to be lower at medium group. Originality/value (state of the art): This study provides a nascent overview of digital literacy level in Pontianak City, highlighting significant differences between micro and small enterprises. These findings serve as a critical reference for policymakers in designing localized strategies to improve digital literacy and foster economic growth. Keywords: digital literacy, mses, non-formal business, digital business